188 The Cardioprotective Effect of MSC Secreted Protein in an in Vitro Model of Myocardial Injury: the Mechanistic Insight. (31st May 2014) - Ismail, Siti; O'Brien, Timothy; Barry, Frank
Abstract : Background: Cardiovascular disease remains one of the leading worldwide causes of mortality. A therapeutic treatment being explored involves using stem cells (MSC) to regenerate damaged cardiac tissue. This is facilitated by ability of MSC to stimulate the myocardium to regenerate, revascularize and improve cardiac function. We observed that MSCs are activated by the ischaemic environment of the infarct, resulting in secretion of a cascade of factors with cytoprotective potential. We identified a number of therapeutically relevant genes involved in paracrine signalling, by gene expression analysis and mass spectrometry. A novel protein, SC1 was expressed by MSCs within the ischaemic myocardium. Our data indicates that SC1 expression in vitro results in cytoprotective effects, mediated through improved cell survival and viability. The aim of our study was to validate and explore the role and mechanism of SC1 in cardio protection using an in vitro myocardial infarction or ischemia model. Methods: The in vitro cardiomyocytes injury model was established by exposing rat primary neonatal cardiomyocytes and H9c2 cells (a cardiac myoblast cell line) with hydrogen peroxide, with and without the addition of endogenous SC1, followed by a period of recovery. Viability, cytotoxicity and caspase activity were examined to measure the protective effects of SC1. In addition, expression of genes and the corresponding protein levels were also examined. Results: Using the in vitro model of oxidative stress, SC1 treatment, in conjunction with H2O2 treatment, resulted in significant increase in cell viability and a corresponding decrease in caspase 3 activity for up to 6 h recovery post treatment. These results were further confirmed by examining gene and protein expression. Gene array results confirmed the expression of Bcl 2 and Xiap, anti apoptotic genes. Interestingly, upregulation of TNF associated genes such as Traf2, Traf3, NFKb were also observed. SC1 treatment, combined with induced oxidative stress, resulted in a significant increase of pAKT, implicating the PI3K/AKT pathways in SC1 cardio-protection. Elevated levels of anti-apoptotic proteins Bcl-2 and reduction of pro-caspase 3 were also observed, supporting the gene array results. SC1 treatment also induced pro-angiogensis by increasing the number of Pecam1 positive cells in an in vivo matrigel angiogenesis assay. Interestingly, the capillary formation displayed an SC1 dose dependent threshold. Discussion and Conclusion: In this study, we demonstrate that SC1 is a major component of the in vivo secretome of MSCs in ischaemic myocardium. SC1 protected cardiomyocytes via inhibition of apoptosis and regulation of the PI3K/AKT pathway in an in vitro oxidative-induced myocardial injury model. These findings support the hypothesis and the paradigm that understanding the therapeutic effects of MSC, via defining their secretome, will result in the improvement of cardiac regenerative therapies.